Hydrogen Development Strategy for Power Company in Indonesia’s Transportation Sector using Scenario Planning - Hadi, Wahyu Jatmika; Sunitiyoso, Yos (International Journal of Economics Development Research (IJEDR), 2025)
One of the initiatives undertaken by Power Company to promote the NZE had been stated in its mid-term planning for 2024-2028 is the implementation of green hydrogen in transportation sector by developing hydrogen refuelling station and establishing the green hydrogen plant (GHP), producing hydrogen with the excess capacity of 124 tons per year. This excess hydrogen has been targeted to be one of revenue resources in beyond kWh, but Power Company had not been established the roadmap. Conversely, the National Roadmap of Hydrogen and Ammonia (RHAN) had been launched by government, targeting 3,690 tons hydrogen utilization per year in transportation sector by 2035 and FECV commercialization stage starting from 2031. The objective of this study is to formulate an appropriate strategy for Power Company in utilizing excess hydrogen in the transportation sector through scenario planning approach. Data are analyzed using PESTLE, Porter’s Five Forces, and semi-structured interview to formulate 2x2 matrix based on the main uncertainties. Four scenarios have been formulated which are called Going Highway, Queueing Tickets, Asking Innovations, and Entering Rest Area as combination of government support and the economic of hydrogen. Shifting to other scenarios should follow the key leading indicators and adjustment to recent working plans need to be done. This study approach can be used as reference for hydrogen producers or policymakers to construct the balanced strategy for hydrogen business development.